PERJANJIAN EKSTRADISI ANTARA INDONESIA DENGAN SINGAPURA DI TINJAU DARI HUKUM PIDANA - Irwan Sapta Putra; Yunawati Karlina (LPPM Universitas Bina Bangsa, 2022)
The number of perpetrators of criminal acts in Indonesia who fled to other countries, especially to Singapore to avoid the entanglement of criminal law resulted in obstacles for Indonesian law enforcement officers to enforce the law against the perpetrators of these crimes. This study is to find out 1. What is the impact of the extradition treaty between Indonesia and Singapore on the perpetrators of criminal acts 2? To find out the contents of the extradition treaty between Indonesia and Singapore. This research method is normative legal research, where the author collects reading materials from books, magazine articles both printed and online, seminar papers, on extradition and legislation in the field of criminal law related to extradition. The nature of this research is descriptive, analyzes and examines, explains the extradition treaty between Indonesia and Singapore in terms of criminal law. Sources of data in this study using primary, secondary and tertiary data sources. Research Results a. The impact of the extradition agreement between Indonesia and Singapore on criminals is that it can narrow the space for criminals in Indonesia to escape. The reason is, Indonesia already has agreements with partner countries in the region including Malaysia, Thailand, the Philippines, Vietnam, Australia, the Republic of Korea, the People's Republic of China, and Hong Kong SAR, and also the perpetrators of criminal acts who fled to Singapore can be extradited to Indonesia by the government. Singapore following a request for extradition by the Indonesian government. b. The contents of the extradition agreement between Indonesia and Singapore according to this Extradition Agreement amount to 31 types, including criminal acts of corruption, money laundering, bribery, banking, narcotics, terrorism, and financing activities related to terrorism. Suggestion With the extradition agreement between Indonesia and Singapore which was signed on Tuesday, January 25, 2022 in the Bintan archipelago, which was attended by the president of Indonesia and the prime minister of Singapore, represented by the Indonesian minister of law and human rights, to follow up on this so that the DPR RI immediately ratify the extradition treaty by immediately ratifying it as a law so that it can be put into effect immediately